Are warbles and bots related to reproductive status in West Greenland caribou? - Cuyler, Christine; White, Robert R.; Lewis, Keith; Soulliere, Colleen; Gunn, Anne; Russell, Don E.; Daniel, Colin (Rangifer, 2012)
In March-April 2008-09, using CARMA protocols, 81 cows and 16 calves were collected in West Greenland from two caribou populations; Akia-Maniitsoq (AM) and Kangerlussuaq-Sisimiut (KS). In both populations, warble larvae numbers were highest in calves and higher in non-pregnant than pregnant cows. Nose bots showed no relationship with pregnancy or lactation; KS calves had higher nose bot loads than cows, a pattern not observed in AM. Pregnant cows had more rump fat than non-pregnant cows. KS cows lacking rump fat entirely had the highest warble burdens. We observed lactating pregnant cows with moderate larval burdens. Projected energy cost of the heaviest observed combined larvae burdens was equivalent to 2-5 days basal metabolic rate (BMR) for a cow, and 7-12 days BMR for a calf. Foregone fattening in adult cows with average burdens was 0.2 to 0.5 kg, but almost doubled with the heaviest infestations to 0.4 and 0.8 kg. Average burdens in calves resulted in forgone fattening of about 0.5 kg, with peak costs equivalent to 0.7 and 1.1 kg fat for AM and KS calves respectively. Although modest, these projected energy costs of hosting larvae for cows support the negative relationship between rump fat and larvae burden. For calves, hosting high burdens of warble larvae could affect winter survival, specifically those weaned normally in October or in early winter. Harmful effects of oestrid larvae burdens may remain subtle but clearly cumulative in relation to seasonal forage availability and incidence of other parasites.